The competitiveness of tropical agriculture : a guide to competitive potential with case studies - Norton, Roger D. , 1942-; Angel, Amy; Arguello, Ricardo; Martinez, Hector; Samaca, Henry; Turner, Anne (Academic Press, 2017)
"The Competitiveness of Tropical Agriculture: A Guide to Competitive Potential with Case Studies describes and synthesizes existing methodologies for evaluating competitiveness in agriculture, introduces extensions and refinements, and provides a novel